2006
DOI: 10.5194/nhess-6-1-2006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of slope instability in the Southwestern Adriatic Margin

Abstract: Abstract. The Southwestern Adriatic Margin (SAM) shows evidence of widespread failure events that generated slide scars up to 10 km wide and extensive slide deposits with run out distances greater than 50 km. Chirp-sonar profiles, side-scan sonar mosaics, multibeam bathymetry and sediment cores document that the entire slope area underwent repeated failures along a stretch of 150 km and that masstransport deposits, covering an area of 3320 km 2 , are highly variable ranging from blocky slides to turbidites, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 43 publications
2
49
1
Order By: Relevance
“…The Multi Beam data confirm the main features denoted by the Single-Beam data but also add relevant information to the SAM ; (B) shelf-indenting submarine slide with large blocks (Minisini et al, 2006); (C) deeply-incised Bari canyon with abandoned channel-levee complex down slope . GS: Gondola Slide; DS: Dauno Seamount; BCS: Bari Canyon System.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The Multi Beam data confirm the main features denoted by the Single-Beam data but also add relevant information to the SAM ; (B) shelf-indenting submarine slide with large blocks (Minisini et al, 2006); (C) deeply-incised Bari canyon with abandoned channel-levee complex down slope . GS: Gondola Slide; DS: Dauno Seamount; BCS: Bari Canyon System.…”
Section: Discussionsupporting
confidence: 66%
“…GS: Gondola Slide; DS: Dauno Seamount; BCS: Bari Canyon System. slope, showing: (1) the blocky nature of the mass-failure features emanating from multiple slide scars (Minisini et al, 2006); (2) the large variety of erosional and depositional bottom-current features (Verdicchio & Trincardi, 2006); (3) the Bari Canyon System (BCS), acting as the main sediment conduit since the Last Glacial Maximum ; and (4) the Dauno Seamount, the main structural feature on the slope, flanked by erosional moats recording the impact of bottom-hugging density currents .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We remark, however, that if the tsunami was induced by a submarine landslide, the source can very unlikely be located in the place suggested by Bedosti (1980) so close to the coast. Recent investigations show that this area is not susceptible to large offshore mass failures (Trincardi et al, 2004), while evidence for widespread failures has been found in the south-western Adriatic margin (Minisini et al, 2006) more than 100 km offshore south of Gargano, where steep slopes link the shallow Adriatic platform to the deep Ionian sea. Anomalous disturbances were also seen on the eastern coast of the Adriatic Sea: at Bar (30 cm), Dubrovnik (40 cm) and Split (45 cm) (Zoe-Armanda, 1988;Papadopoulos, 1993).…”
Section: Italian Tsunami Catalogue: Tsunami Events In Central Adriaticmentioning
confidence: 99%
“…Their contribution to tsunami generation can be conspicuous, but can be predicted only if the location and size of the landslide is known with sufficient accuracy. Minisini et al (2006) show that in the Southern Adriatic Sea slope instability could have played a relevant role in tsunami generation in historical and prehistorical times.…”
Section: Wave Propagationmentioning
confidence: 94%